2015
DOI: 10.1021/acs.jafc.5b05289
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Lipids in the Grain of Wheat (cv. Hereward) Determined by Lipidomic Analysis of Milling and Pearling Fractions

Abstract: Lipidomic analyses of milling and pearling fractions from wheat grain were carried out to determine differences in composition that could relate to the spatial distribution of lipids in the grain. Free fatty acids and triacylglycerols were major components in all fractions, but the relative contents of polar lipids varied, particularly those of lysophosphatidylcholine and digalactosyldiglyceride, which were enriched in flour fractions. By contrast, minor phospholipids were enriched in bran and offal fractions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 39 publications
8
64
0
Order By: Relevance
“…On the other hand, the higher presence of TAG detected in L3, M1, and M2 revealed that these types of by‐products could be used for extraction of useful oil for nutraceutical, pharmaceutical, cosmetic, and food industry; however, it should be pointed out that TAG in L3 and M1 was drastically hydrolyzed after 15 days of storage. The present results agree with those reported by González‐Thuillier et al which confirm the higher presence of FFA in the outer layer with respect to the inner one, where TAG are more concentrated since they are the major forms of storage lipids. In general, DAG were less abundant than TAG and, in agreement with literature data, a decreasing trend in DAG concentration was observed going from the outer part of the grain to the inner one.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, the higher presence of TAG detected in L3, M1, and M2 revealed that these types of by‐products could be used for extraction of useful oil for nutraceutical, pharmaceutical, cosmetic, and food industry; however, it should be pointed out that TAG in L3 and M1 was drastically hydrolyzed after 15 days of storage. The present results agree with those reported by González‐Thuillier et al which confirm the higher presence of FFA in the outer layer with respect to the inner one, where TAG are more concentrated since they are the major forms of storage lipids. In general, DAG were less abundant than TAG and, in agreement with literature data, a decreasing trend in DAG concentration was observed going from the outer part of the grain to the inner one.…”
Section: Discussionsupporting
confidence: 93%
“…The present results agree with those reported by González‐Thuillier et al which confirm the higher presence of FFA in the outer layer with respect to the inner one, where TAG are more concentrated since they are the major forms of storage lipids. In general, DAG were less abundant than TAG and, in agreement with literature data, a decreasing trend in DAG concentration was observed going from the outer part of the grain to the inner one.…”
Section: Discussionsupporting
confidence: 93%
“…Other high ranking positively correlated lipids also belong to the higher abundant representatives of their subclasses (Table S3 “Median intensity”). With few exceptions, the lipids consisted of FAs with 16 or 18 carbon atoms, which are typical of wheat/plant seed lipids (González‐Thuillier et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with a previous study [4], as einkorn was reported to show a richer lipid profiling among the ancient varieties, a lipid content 50% higher than those of bread wheat. In fact, PC 34:2 together with lysoPC 16:0 and lysoPC 18:2 are the major PC species detected, representing 60%–70% of the total wheat PC [28]. Acyl carbon and double-bond configurations in phospholipids are probably combination of the major fatty acids, that in einkorn are reported to be linoleic (18:2), oleic (18:1), and palmitic (16:0) acids [4].…”
Section: Discussionmentioning
confidence: 99%